Dynamic Electrodeposition of Manganese Dioxide: Temporal Variation in the Electrodeposition Mechanism. Issue 5 (1st January 2016) - Gibson, Andrew J.; Johannessen, Bernt; Beyad, Yaser; Allen, Jessica; Donne, Scott W.
Abstract : The time resolved mechanism of electrodeposition and the effect of this changing mechanism on the nucleation and growth of solid manganese dioxide has been investigated in both acidic and neutral electrolytes on the rotating ring disc electrode (RRDE). The fate of the Mn 3+ intermediate is a key feature of this electrodeposition mechanism, the formation of which is dependent on the substrate, which in this case is either platinum, MnO2 or MnOOH. On the platinum surface, for all electrolytes, soluble Mn 3+ is produced initially. The stability of this soluble Mn 3+ species determines the initial morphology, and rate of change of mechanism for the process. In a neutral electrolyte, nucleation and growth of MnO2 occurs primarily through the precipitation of a 2D film of MnOOH on the platinum, which rapidly covers the surface. Nucleation in an acidic H2 SO4 system occurs primarily via a disproportionation route which forms 3D MnO2 hemispheroids that cover the substrate slowly. Subsequent growth of MnO2 in both electrolytes then proceeds via formation of a MnOOH film, which is subsequently oxidized in the solid state to form MnO2 . MnOOH oxidation to MnO2 appears kinetically limited, which is overall a limiting factor in the electrodeposition process.